Pengaruh Beban Kerja dan Kompensasi terhadap Intention to Stay dengan Kepuasan Kerja sebagai Mediasi - Ramadhan, Ashriansyah; Rosnani, Titik; Hasanudin, Hasanudin; Jaya, Arman (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the effect of workload and compensation on intention to stay, both directly and through the mediation of job satisfaction among modern Coffee Shop employees in Pontianak City. The population of this study consists of modern coffee shop employees in Pontianak, with a sample of 172 respondents. The data analysis method uses Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The results show a significant negative effect of workload on job satisfaction and intention to stay, a significant positive effect of compensation on job satisfaction and intention to stay, a significant effect of job satisfaction on intention to stay, and a mediating role of job satisfaction in the relationship between workload and compensation with intention to stay. This study is expected to contribute to coffee shop management in Pontianak by encouraging attention to workload and compensation in order to improve employee job satisfaction and intention to stay.